Method of identification of dedicated computer networks for computer systems of objects of oil and gas complex - Бабчук, Сергій Миронович (Eastern-European Journal of Enterprise Technologies, 2013)
For many years the automation systems used to be constructed on the basis of analogue devices. However, in the conditions of rapidly growing production of micro processing systems, multiple nodes dedicated computer networks that digitally exchange data emerged as an alternative solution. Nowadays, the companies of the world use more than hundred different dedicated computer networks. During modernization period the companies need to choose optimal decisions for specific technological areas. However, at present time, methodological background for effective solution of mentioned problem practically does not exist. There has been done research of the existing dedicated computer networks. We have developed classification of dedicated computer networks that can be used on the objects of oil and gas complex. Also, there was created selection algorithm of dedicated computer network for computer systems of the objects of oil and gas complex. We have developed method of identification of dedicated computer networks for computer systems of objects of oil and gas complex. Thus, we have created a methodological background that will assist enterprises in their choice of optimal decisions for specific technological areas.